Efektivitas Sosialisasi Program Bank Sampah dalam Mendorong Partisipasi Masyarakat: Studi Kasus di Kelurahan Dusun Besar Kota Bengkulu - Solin, Enjelina; Muhrosi, Muhammad Arif; Saputra, Fitrawan Aldi; Safitri, Awiya Anggriani; Mahesa, Nauvaldi Anugrah; Marshanda; Puspitasari, Dinda; Rosana, Elvira (UNIB Press, 2025)
The Waste Bank Program is a community-based waste management initiative aimed at reducing waste volume and increasing environmental awareness among residents. This study aims to examine the effectiveness of the initial socialization of the Waste Bank Program in encouraging community participation in Dusun Besar Village, Bengkulu City. The method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation involving the village authorities, waste bank managers, as well as residents who are both involved and not yet involved in the program. The research findings indicate that socialization efforts carried out through community meetings, social media, and direct counseling were fairly successful in reaching most of the community. However, the level of participation remains moderate due to obstacles such as a lack of technical understanding, limited supporting facilities, and uneven distribution of information. Therefore, the effectiveness of the socialization can be considered moderately successful but needs improvement through more intensive, participatory, and community-based communication strategies. These findings are expected to serve as a reference for local governments and community managers in optimizing the implementation of the Waste Bank Program in the future.